2020
DOI: 10.1080/14616696.2020.1839671
|View full text |Cite
|
Sign up to set email alerts
|

Who is most affected by the Corona crisis? An analysis of changes in stress and well-being in Switzerland

Abstract: This study analyses the consequences of the Covid-19 crisis on stress and wellbeing in Switzerland. In particular, we assess whether vulnerable groups in terms of social isolation, increased workload and limited socioeconomic resources are affected more than others. Using longitudinal data from the Swiss Household Panel, including a specific Covid-19 study, we estimate change score models to predict changes in perceived stress and life satisfaction at the end of the semi-lockdown in comparison to before the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 22 publications
9
69
3
Order By: Relevance
“…As for resilience, changes experienced in the world of work did reflect on the respondents' level of concern about the gravity of situation caused by COVID-19. While unlike Kuhn et al (2020) we found no direct effect of wage reduction, having workload reduced and experiencing deterioration in work-life balance both contributed to the level of concern, as did being employed in private sector. Yet the experience of state support via wage subsidies went some way to reduce the concern.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…As for resilience, changes experienced in the world of work did reflect on the respondents' level of concern about the gravity of situation caused by COVID-19. While unlike Kuhn et al (2020) we found no direct effect of wage reduction, having workload reduced and experiencing deterioration in work-life balance both contributed to the level of concern, as did being employed in private sector. Yet the experience of state support via wage subsidies went some way to reduce the concern.…”
Section: Discussioncontrasting
confidence: 90%
“…More frequent or intensive income loss for the younger, low-waged, and for workers in marginal employment was a common finding in most studies that addressed the issue (Beland et al, 2020 for Canada; Holst et al for Germany, Crossley et al, 2021 for UK). Income loss might in particular incur other hardships, a linkage confirmed in this case by findings of a Swiss household panel study, suggesting that change in financial situation during the initial wave of the pandemic triggered both increased stress and life (dis)satisfaction (Kuhn et al, 2020).…”
Section: Work-related Events During the Pandemicsupporting
confidence: 61%
See 1 more Smart Citation
“…Heightened risk perception was also linked to ethnic and racial otherness, and (un)employment (Soiné et al 2020). Psychological consequences were especially dramatic following the social gradient, with a more pronounced effect among the lower educated social strata, vulnerable groups struggling with social isolation such as young adults, COVID-19 risk group members, single people, people with higher workloads (generally, women), and those with depleted socioeconomic resources (the unemployed and those who had experienced a deteriorating financial situation) (Kuhn et al 2020).…”
Section: Psychological Aspectswell-being and Resilience Vs Stress Anmentioning
confidence: 99%
“…Changes to working conditions due to the crisis, such as partial or full unemployment, loss of revenue and having to work primarily from home, may also have led to the COVID-19 crisis causing different psychological effects. For example, working from home may protect employees from infection with COVID-19 [1,9], and two studies from Austria and Switzerland also identified the possibility to work from home as a protective factor the psychological impact of the COVID-19 crisis [9,25], although in the second study this was only the case for one indicator (perceived stress measured with one question) and before adjustment for socioeconomic resources. However, working mostly from home may also lead to more social isolation and thus to increased stress.…”
Section: Introductionmentioning
confidence: 99%